The Influence of Transformational, Transactional, and Servant Leadership on Sustainable Organizational Performance: An Empirical Study in Indonesian Higher Education - Saputro, Seno Hadi; Supriyanto, Bambang Eko; Setiyowati, Harlis (Baca Dulu Publisher, 2025)
This study examines the influence of transformational, transactional, and servant leadership on sustainable organizational performance at Institut Sains dan Bisnis Atma Luhur, Indonesia. Using a census technique involving the entire population of faculty and educational staff, this quantitative research employed multiple linear regression analysis to test the hypothesized relationships. The findings reveal that while the three leadership styles collectively influence sustainable organizational performance, only servant leadership demonstrates a significant individual effect. Transformational and transactional leadership showed no significant direct effects on sustainable performance. These counterintuitive findings challenge the dominant transformational leadership paradigm prevalent in management literature and highlight the critical importance of servant leadership in knowledge-intensive organizations. The study suggests that servant leadership's emphasis on empowerment, stewardship, trust-building, and people-centered culture aligns better with the nature of academic work characterized by high professional autonomy and intrinsic motivation. The findings also resonate with Indonesian collectivistic cultural values that emphasize harmony and relationships. Practical implications include prioritizing servant leadership competency development at all organizational levels and adopting a comprehensive systemic approach to achieving institutional sustainability beyond leadership factors alone